2016
DOI: 10.1007/s11367-016-1182-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating human toxicity potential of land application of sewage sludge: the effect of modelling choices

Abstract: Purpose Many municipalities are facing increasing pressure to adapt solid waste and wastewater management infrastructures in order to better close nutrient cycles. The focus of this study is on the estimation of the human toxicity potential associated with chemical contaminants released upon the application of sewage sludge to agricultural land. More specifically, this study investigated the effect of modelling choices regarding fate and exposure assessment. Methods Monitoring data were collected for contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…All of these studies carried out using USES-LCA to assess terrestrial ecotoxicity inevitably inherit the shortcomings of that model, including the lack of ability to extrapolate aquatic data to estimate terrestrial ecotoxicity. Harder et al (2017) studied the USEtox-modelled effects on human toxicity and compared the results with regard to sludge spread on soil. In the context studied, 13 organic contaminants were found to be of greatest potential concern, including bis(2-ethylhexyl) phthalate, hexachlorobenzene, 1 PCB, 1 polybrominated diphenyl ether, 17α-ethinyloestradiol, 7 PAH and one biocide (Mirex, CAS No.…”
Section: Ecotoxicity Of Ow-borne Organic Contaminantsmentioning
confidence: 99%
“…All of these studies carried out using USES-LCA to assess terrestrial ecotoxicity inevitably inherit the shortcomings of that model, including the lack of ability to extrapolate aquatic data to estimate terrestrial ecotoxicity. Harder et al (2017) studied the USEtox-modelled effects on human toxicity and compared the results with regard to sludge spread on soil. In the context studied, 13 organic contaminants were found to be of greatest potential concern, including bis(2-ethylhexyl) phthalate, hexachlorobenzene, 1 PCB, 1 polybrominated diphenyl ether, 17α-ethinyloestradiol, 7 PAH and one biocide (Mirex, CAS No.…”
Section: Ecotoxicity Of Ow-borne Organic Contaminantsmentioning
confidence: 99%
“…The environmental impacts of sludge use in agriculture have recently attracted attention in several modelling studies, e.g. for toxicity assessments (Harder et al, 2016) and pathogen risk (Harder et al, 2014). Heimersson et al (2016) showed that the modelling of N, P and major C flows originating from the wastewater is very important in LCA, since the type of wastewater treatment process determines whether they end up as an emission, contributing to environmental impacts, or as a resource flow and thereby possibly lowering or counteracting environmental impacts from the assessed system.…”
Section: Modelling Of Agricultural Sludge Use In Lcamentioning
confidence: 99%
“…The land application of sludge involves effects on soil properties, soil microbes, plants, and animal by the accumulation of these pollutants. This may threaten the safety of agricultural production and human health through the food chain (Pritchard et al 2010;Bondarczuk et al 2016;Harder et al 2016). Thus, the use of sewage sludge as a source of plant nutrients for crop production needs to be carried out carefully to protect the environment and human health.…”
Section: Introductionmentioning
confidence: 99%